Economic evaluation of treatments for patients with localized prostate cancer in Europe: a systematic review. Issue 1 (December 2016) - Becerra, Virginia; Ávila, Mónica; Jimenez, Jorge; Cortes-Sanabria, Laura; Pardo, Yolanda; Garin, Olatz; Pont, Angels; Alonso, Jordi; Cots, Francesc; Ferrer, Montse
Abstract Background Our objective was to assess the efficiency of treatments in patients with localized prostate cancer, by synthesizing available evidence from European economic evaluations through systematic review. Methods Articles published 2000–2015 were searched in MEDLINE, EMBASE and NHS EED (Prospero protocol CRD42015022063). Two authors independently selected studies for inclusion and extracted the data. A third reviewer resolved discrepancies. We included European economic evaluations or cost comparison studies, of any modality of surgery or radiotherapy treatments, regardless the comparator/s. Drummond's Checklist was used for quality assessment. Results After reviewing 8, 789 titles, 13 European eligible studies were included: eight cost-utility, two cost-effectiveness, one cost-minimization, and two cost-comparison analyses. Of them, five compared interventions with expectant management, four contrasted robotic with non robotic-assisted surgery, three assessed new modalities of radiotherapy, and three compared radical prostatectomy with brachytherapy. All but two studies scored ≥8 in the quality checklist. Considering scenario and comparator, three interventions were qualified as dominant strategies (active surveillance, robotic-assisted surgery and IMRT), and six were cost-effective (radical prostatectomy, robotic-assisted surgery, IMRT, proton therapy, brachytherapy, and 3DCRT). However, QALY gains in most of them were small. For interventions considered as dominant strategies, QALY gain was 0.013 for active surveillance over radical prostatectomy; and 0.007 for robotic-assisted over non-robotic techniques. The highest QALY gains were 0.57–0.86 for radical prostatectomy vs watchful waiting, and 0.72 for brachytherapy vs conventional radiotherapy. Conclusions Currently, relevant treatment alternatives for localized prostate cancer are scarcely evaluated in Europe. Very limited available evidence supports the cost-effectiveness of radical prostatectomy over watchful waiting, brachytherapy over radical prostatectomy, and new treatment modalities over traditional procedures. Relevant disparities were detected among studies, mainly based on effectiveness. These apparently contradictory results may be reflecting the difficulty of interpreting small differences between treatments regarding QALY gains.